CircRNA ANXA2 Promotes Lung Cancer Proliferation and Metastasis by Upregulating PDPK1 Expression. (28th December 2021) - Ju, Yan; Yuan, Bin; Wu, Wenan; Zhao, Jin; Shi, Xiaorui
Abstract : Lung cancer is a common malignant tumor that seriously threatens human health. It has become the top malignant tumor in terms of morbidity and mortality. In recent years, circRNA, a special noncoding RNA molecule, has attracted considerable interest. This study focused on the role of circRNA ANXA2 (circANXA2) in lung cancer and the molecular mechanism of cancer promotion. Real-time quantitative PCR (RT-PCR) was used in detecting the expression abundance of circANXA2 in different lung cancer cells and tissues. The subcellular localization of circANXA2 was detected through fluorescence in situ hybridization. circANXA2 expression was knocked down through siRNA. CCK-8, clone formation assay, and TUNEL assay were used in evaluating the effects of circANXA2 on cell proliferation, clone formation ability, and apoptosis. The role of circANXA2 in tumor proliferation was further verified in vivo using the tumor transplantation model in nude mice. The molecular mechanism of circANXA2 was investigated with luciferase activity assay and RT-PCR. The expression abundance of circANXA2 is high in lung cancer cell lines and tissues. Knocking down of circANXA2 inhibits the proliferation and clonogenesis of the lung cancer cells. Knocking down circANXA2 promotes apoptosis. circANXA2 further affects downstream PDPK1 expression by regulating miR-33a-5p and thereby affecting the malignancy of the lung cancer cells. circANXA2 inhibits miR-33a-5p activity by directly interacting with miR-33a-5p. circANXA2 regulates the transcription of the miR-33a-5p downstream target gene PDPK1 and affects the malignant progression of lung cancer.